REGULASI PASAL 485 DALAM HUKUM POSITIF DAN HUKUM ISLAM PADA PENANGGULANGAN CYBER SEX - Yusnani Yusnani; Reinaldi Reinaldi; Magfirah Magfirah (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2017)
The interesting thing with criminalization is watching videos of sex scenes impacting on the collapse which is usually called by term “buffalo gathering” which is destroying morals; it is a social reality raises problematic but its rules have not been touched by law and the Law. The Criminal Code Draft, article 485 about buffalo gathering is not implemented and the proposal for the closure of pornographic access. This research is done by using empirical normative legal research methods, that is interview to the RUU team, socialization to local leaders, customary leaders, police officers and legislation as well as parents and academics. The results of the study show that local governments support the rejection of pornographic activities bill which is stated in article 485, the authority of total termination depends on the Communication and Information Office in Jakarta. To anticipate the emergency of adultery is expected to apply the addition of hours of religious learning for students from grade 4-6 primary school to Higher Education, male students must stay at the mosque at least 1 (one) night each week to study the Qur'an Fiqh, traditions hadith duty as muezzin and prayer priest. Students study in the daytime certified. One of the requirements for the increase of classes in public schools